HUBUNGAN KUALITAS INFORMASI DAN KREDIBILITAS SUMBER INFORMASI TERHADAP TINGKAT KEPERCAYAAN INFORMASI KESEHATAN PADA TIKTOK OLEH GENERASI Z - Audrey Marsanda, Marchella; Noor Rakhmad, wiwid; Naryoso, Agus (Interaksi Online, 2024)
This study explores the credibility and trustworthiness of health information provided by TikTok influencer Ayman Alatas (@aymanalts) amidst the proliferation of health-related hoax on social media. By applying Information Integration Theory, it examines the relationship between the quality of information, source credibility, and the level of trust among 122 Generation Z respondents from Jakarta who watched Ayman Alatas’s TikTok content. The findings reveal that respondents perceive Ayman Alatas's health information as highly credible and of substantial quality, demonstrating a strong positive correlation between these factors and the trust placed in the information. Despite the widespread presence of health hoaxes, Generation Z exhibits a commendable ability to critically evaluate the information they encounter, effectively mitigating the impact of misinformation. The study concludes that Ayman Alatas successfully fosters trust through his high-quality health education and recommends he leverage additional TikTok features to further enhance the dissemination of reliable health information.